Social Psychology of Disaster Survivors: Case Study of Pekalongan, Indonesia Flood-Affected Residents - M. Yasin Abidin; Rofiqotul Aini; Ahmad Ta'rifin; Siska Rakhmawati (Kuras Institute, 2025)
Tidal flooding has become a chronic environmental problem in Simonet Hamlet, Pekalongan, causing daily inundation of up to one meter and accelerating coastal erosion. This study aims to analyze the forms of suffering experienced by affected residents, identify the social-psychological trauma caused by prolonged tidal flooding, and describe the coping strategies used by the community. This research employs a qualitative method using interviews, observations, and documentation, while data were analyzed with an interactive model. The results show that residents experience multidimensional losses, including the destruction of houses and land, restricted mobility due to isolation, declining health conditions, loss of stable employment, and increased socio-economic burdens. The social-psychological impacts include recurring trauma during flood events, stress related to submerged homes and unstable livelihoods, forced job diversification, and the loss of long-term aspirations. To cope with these conditions, residents adopt physiological and psychological adaptation strategies and periodically evacuate to higher ground. The findings underscore the need for integrated disaster-management policies and psychosocial support to strengthen community resilience in chronically flooded coastal areas.